Analisa Penerapan Strategi All-Financial Management Pada Bank Rakyat Indonesia di Era Global - Agus Mujiyono; Suryana Agus Nasrudin (xxxx-xxxx, 2021)
This study uses qualitative methods in the form of literature review with descriptive analysis and banking operational observations, namely a process to produce in-depth knowledge of the 'world of bank management' with the aim of explaining the implementation of all financial management strategies at BRI Tbk in an effort to win competition in the global era. The all-financial management strategy is a combination of several management management related to working capital management, cash and securities management, cash flow management in and out, accounts receivable management, inventory management-, short- and medium-term funding management, credit policy to marketing strategies implemented that lead to on financial condition and focus on increasing profit. BRI Tbk is a financial institution that is always concerned with managing customers' money. It requires complete financial management that is profit-oriented and has a sustainable existence by becoming an Integrated Financial Solution. The implementation of all management finance at BRI Tbk is influenced by internal and external factors. The internal is supported by the strengthening of work culture and innovation, while the external is by always updating the development of competing banks and partnering with the government in an effort to strengthen the bank management ecosystem. By implementing the all-financial management strategy of BRI, it is hoped that operational costs can be reduced and profits will increase and be able to provide the best service for the community.